Efisiensi Proses Pelaporan Keuangan yang dimediasi Digitaliasi Akuntansi terhadap Akurasi Laporan Keuangan UMKM Kota Semarang - Yolandha Raharjo; Parju, Parju; Setyobudi, Setyobudi; Nurchayati, Nurchayati (Jurnal Ekonomi Manajemen Akuntansi, 2025)
The use of technology in the digitalization era is increasingly important in aspects of human life, one of which is in the field of accounting and business. Efficiency in the financial reporting process and accounting digitalization are important factors in influencing the accuracy of financial statements. This study aims to examine the effect of the efficiency of the financial reporting process mediated by accounting digitization on the accuracy of MSME financial reports in Semarang City. This study uses a quantitative approach with data collected through questionnaires from MSMEs in Semarang City. The population of this study amounted to 123 incorporated MSMEs and the research sample was MSMEs that had digitized their financial records (purposive sampling method), totaling 94 MSMEs in Semarang City. The results showed that the efficiency of the financial reporting process has a positive impact on accounting digitalization. However, the efficiency of the financial reporting process does not have a significant impact on the accuracy of MSME financial reports. Meanwhile, accounting digitalization has a positive impact on the accuracy of MSME financial statements.